A protocol to establish and maintain organotypic cerebellar slice culture (OCerSC) from aged mice - Michael F. Almeida; Kaitlan Smith; Michael A. Garris; Rebekah Sanchez-Hodge; Meagan Colie; Jonathan C. Schisler (PLoS ONE, 2026)
Organotypic slice culture is a sophisticated technique historically used in cellular and developmental neurobiology to investigate three-dimensional architecture and cellular interactions. Maintaining thin tissue slices preserves organotypic structure and more accurately reflects the in vivo microenvironment than traditional monolayer cell cultures. These models are crucial in neurobiology, especially for studying age-dependent neurodegenerative disorders. However, preserving tissue viability in organotypic slices from adult brain tissue remains challenging. This protocol focuses on culturing organotypic slices from adult cerebellar tissue to address the critical need for discovery within this brain region. The cerebellum’s unique cellular architecture and specialized circuitry have made culturing organotypic slices challenging. This protocol presents a novel finding: careful manipulation of culture conditions reduces early neuroinflammatory responses, enhances cerebellar tissue viability, and promotes the long-term maintenance of well-preserved cerebellar slices. This innovative system enables detailed analyses of neuronal morphology and functional connectivity at both cellular and circuit levels, incorporating advanced imaging and electrophysiological techniques to fulfill a critical need in neurobiology.